Enslaved African Labour in the Americas: from primitive accumulation to manufacture with racial violence (Revista de Estudos e Pesquisas sobre as Américas, 2018)
This paper reconceptualises Marx’s value theory in an analysis of the enslavement of African Americans as a part of the capitalist mode of production with its own special characteristics. Synthesising from the literature, I argue that sugar plantation slavery from the sixteenth into the nineteenth century had a duel relation concerning the debate over primitive accumulation vs. capitalism from the start. The plantation did represent an early form of specifically capitalist production, in that the enslaved African’s labour power was purchased in order to create new surplus value in the production of commodities, but also relying on continual European looting of Africa to provide that labour power. The paper addresses the gap between two conventional Marxist readings of the relation between capitalism and the enslavement of Africans. The first reading sees slavery as part of the process of primitive accumulation of capital, the ‘original sin’ of dispossession. The second reading sees capitalism as such as exclusively based on the exploitation of ‘free’ wage labour as its general condition. The paper provides a third interpretation that sees enslavement as a racialised mode of exploitation with a division of labour similar to manufacture. This approach demonstrates continuities as well as changes from sugar plantation slavery in Latin America and the Caribbean on to cotton slavery in the US South.Keywords: Primitive Acumulation ”“ Enslaved African Labour ”“ Marx Value Theory ”“ Latin AmericaTrabalho Escravo Africano nas Américas: a violência racial da acumulação primitiva Ã  manufatura Resumo Este artigo re-conceitualiza a teoria do valor de Marx em uma análise da escravização dos afro-americanos como parte do modo de produção capitalista com suas próprias características especiais. Sintetizando a partir da literatura, defendo que a escravidão das plantações de cana dos séculos XVI a XIX tinha uma relação dual a respeito do debate sobre a acumulação primitiva versus o capitalismo desde o início. A plantation representou uma forma primitiva de produção especificamente capitalista, na qual a força de trabalho africana escravizada foi comprada para criar nova mais-valia na produção de mercadorias, mas também contando com a contínua pilhagem europeia da África para fornecer essa força de trabalho. O artigo aborda a lacuna entre duas leituras marxistas convencionais sobre a relação entre o capitalismo e a escravização dos africanos. A primeira leitura vê a escravidão como parte do processo de acumulação primitiva do capital, o "pecado original" da expropriação. A segunda leitura vê o capitalismo como tal exclusivamente baseado na exploração do trabalho assalariado "livre" como condição geral. O artigo fornece uma terceira interpretação que vê a escravização como um modo racializado de exploração com uma divisão do trabalho semelhante Ã  manufatura. Essa abordagem demonstra continuidades e mudanças da escravidão na América Latina e no Caribe para a escravidão do algodão no sul dos EUA.Palavras-chave: Acumulação Primitiva ”“ Trabalho Escravo Africano ”“ Teoria do Valor de Marx ”“ América LatinaTrabajo Esclavo Africano en las Américas: la violencia racial de la acumulación primitiva a la manufacturaResumen Este artículo reconceptualiza la teoría del valor de Marx en un análisis de la esclavización de los afroamericanos como parte del modo de producción capitalista con sus propias características especiales. Sintentizando desde de la literatura, argumento que la esclavitud em las plantations de azúcar desde el siglo dieciséis hasta el siglo diecinueve tuvo una relación de duelo con respecto al debate sobre la acumulación primitiva frente al capitalismo desde el principio. La plantation representó una forma primitiva de producción específicamente capitalista, en la que se compraba la fuerza de trabajo africana esclavizada para crear una nueva plusvalía en la producción de mercancías, pero también se basaba en el saqueo europeo continuo de África para proporcionar esa fuerza de trabajo. El artigo aborda la brecha entre dos lecturas marxistas convencionales de la relación entre el capitalismo y la esclavización de los africanos. La primera lectura ve a la esclavitud como parte del proceso de acumulación primitiva de capital, el "pecado original" de la desposesión. La segunda lectura ve al capitalismo como tal basado exclusivamente en la explotación del trabajo asalariado "libre" como su condición general. El documento proporciona una tercera interpretación que ve a la esclavitud como un modo racializado de explotación con una división del trabajo similar a la fabricación. Este enfoque demuestra las continuidades y los cambios de la esclavitud de las plantaciones de azúcar en América Latina y el Caribe en la esclavitud del algodón en el sur de los Estados Unidos.Palabras-clave: Acumulación Primitiva ”“ Trabajo Esclavo Africano ”“ Teoría del Valor de Marx ”“ América Latina